Targeting Mechanotransduction at the Transcriptional Level: YAP and BRD4 Are Novel Therapeutic Targets for the Reversal of Liver Fibrosis - Zhubanchaliyev, Altynbek; Temirbekuly, Aibar; Kongrtay, Kuralay; Wanshura, Leah C.; Kunz, Jeannette (Frontiers in Pharmacology, 2016)
Liver fibrosis is the result of a deregulated wound healing process characterized by the excessive deposition of extracellular matrix. Hepatic stellate cells (HSCs), which are activated in response to liver injury, are the major source of extracellular matrix and drive the wound healing process. However, chronic liver damage leads to perpetual HSC activation, progressive formation of pathological scar tissue and ultimately, cirrhosis and organ failure. HSC activation is triggered largely in response to mechanosignaling from the microenvironment, which induces a profibrotic nuclear transcription program that promotes HSC proliferation and extracellular matrix secretion thereby setting up a positive feedback loop leading to matrix stiffening and self-sustained, pathological, HSC activation. Despite the significant progress in our understanding of liver fibrosis, the molecular mechanisms through which the extracellular matrix promotes HSC activation are not well understood and no effective therapies have been approved to date that can target this early, reversible, stage in liver fibrosis. Several new lines of investigation now provide important insight into this area of study and identify two nuclear targets whose inhibition has the potential of reversing liver fibrosis by interfering with HSC activation: Yes-associated protein (YAP), a transcriptional co-activator and effector of the mechanosensitive Hippo pathway, and bromodomain-containing protein 4 (BRD4), an epigenetic regulator of gene expression. YAP and BRD4 activity is induced in response to mechanical stimulation of HSCs and each protein independently controls waves of early gene expression necessary for HSC activation. Significantly, inhibition of either protein can revert the chronic activation of HSCs and impede pathological progression of liver fibrosis in clinically relevant model systems. In this review we will discuss the roles of these nuclear co-activators in HSC activation, their mechanism of action in the fibrotic process in the liver and other organs, and the potential of targeting their activity with small molecule drugs for fibrosis reversal.